Asymetrical federalism: theoretical origins and tautology in the term / Federalismo assimétrico: origens teóricas e tautologia no termo - Liziero, Leonam (REVISTA QUAESTIO IURIS, 2020)
This article aims to analyze the theoretical origins of the asymmetrical federalism in the 20th century as a basis for justifying the asymmetries existing in federal States, such as Canada, Germany, Russia and India, and which would justify the de jure asymmetry in symmetric federal states as Brazil. In an article published by Livingston, in his sociological conception of federalism, we find the first writings on asymmetrical federalism, in describing the nature of federalism in society. The first part of the article will look at Livingston's proposal. Then, we proceed to verify the notion delineated by Tarlton, who explores the contrast between the idealism of symmetry and the concreteness of asymmetry in the federative relations. Finally, we will discuss tautology involving the term “asymmetrical federalism”.